(untitled) (Mediscope, 2016)
Urinary iodine excretion increases during pregnancy. Presence of thyroid peroxidase antibody (TPO-Ab) accelerates this excretion rate. The objectives of the study was to observe the relation between TPO-Ab and urinary excretion of iodine in normal pregnant women during 1st trimester. This case-control study was carried out in the Department of Physiology, Sir Salimullah Medical College from 1st January to 31st December 2011. A total number of 120 subjects were included in the study and divided into control group (Group A) and study group (Group B). Group A consisted of 60 healthy non-pregnant women aged between 20 to 35 years. Group B consisted of 60 normal pregnant women of same age range. Group B was further subdivided into Group B1 and Group B2 according to the level of TPO-Ab. Group B1 consisted of 11 TPO-Ab positive pregnant women and Group B2 consisted of 49 TPO-Ab negative pregnant women. Group A was selected from personal contacts and Group B from Out Patient Department of Obstetrics and Gynecology of Sir Salimullah Medical College and Mitford Hospital. For assessment of iodine excretion, urinary iodine concentration, serum TPO-Ab and HCG of all pregnant women was measured by Spectrophotometric method, Microparticle Enzyme Immunoassay and Enzyme- Linked Immunosorbent Assay, respectively. In this study, urinary iodine was significantly (p < 0.001) higher in normal pregnant women during 1st trimester in comparison to those of nonpregnant women. Urinary iodine concentration was significantly (p < 0.001) higher in TPO-Ab positive pregnant women in comparison to those of TPO-Ab negative. Again, urinary iodine concentration showed significant (p < 0.001) positive correlation with that of TPO-Ab. Urinary iodine excretion increased in TPO-Ab positive normal pregnant women during 1st trimester. So, iodine supply should be increased during pregnancy and screening for TPO-Ab should be done routinely during pregnancy. Mediscope Vol. 3, No. 1: January 2016, Pages 28-32